Kekhawatiran dalam Perspektif Teologis, Psikologis, dan Pendidikan Kristiani: Sebuah Tafsir Matius 6:25-34 Interdisipliner - Frans Pantan; Onnie Lumintang; Laura Tarulina (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2023)
Worry is a common feeling that nearly every individual has faced throughout human history. Psychological research has generally shown that worry has a negative impact on both the mental and physical well-being of individuals. There is an implicit call in the belief that humans should not excessively worry about their lives, as found in the text of Matthew 6:25-34. This research seeks to reexamine worry through an interdisciplinary approach, involving its psychological aspects. The Gospel of Matthew is approached through hermeneutic analysis while simultaneously considering its psychological facets, which is referred to as 'interdisciplinary interpretation.' The culmination of this interdisciplinary meeting results in the thesis statement that the text of Matthew 6:25-34, when interpreted through an interdisciplinary lens, teaches that worry, though common to human experience, can be managed and overcome. This interpretive finding subsequently provides a proposal for the development of a Christian pastoral counseling approach to assist individuals in managing their worries.